The date and circumstances of the Heliodoros affair: Considerations on the Seleucus IV dossier from Maresha - Grüll, Tibor (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In 2005 and 2006 in the Hellenistic city of Marise (Marisha/Bet Guvrin, Israel) five adjoining fragments of a Greek inscription has been found. The stele contains three letters: an order from Seleucus IV (187-175 B.C.) to his chancellor Heliodoros about a certain Olympiodoros, who was put in charge of the sanctuaries of Koilē Syria and Phoinikē; a letter from Heliodoros to Dorymenes (who was in all probability the strategos of Koilē Syria and Phoinikē at that time); and a letter from Dorymenes to a certain Diophanes (probably the hyparchos of the district of Marise). The letters are dated to the month Gorpiaios of the year 134 S.E. (summer of 178 B.C.). There is no doubt that Heliodoros in the dossier of Marise, and Heliodoros in the Second Book of Maccabees (ch. 3–4) is the same person who attempted to plunder the Temple of Jerusalem, but according to the 2Macc 3:25–27 he has suffered a divine punishment. In this paper I am arguing that the “Heliodoros-affair” happened in the earlier years of Seleucus IV’s reign, probably nine or eight years before Olympiodoros was put in charge of religious affairs in Koilē Syria and Phoinikē. If we accept this chronological order, the known list of four strategoi of Koilē Syria and Phoinikē can be easily put together.